Whole-Blood Mitochondrial DNA Copies Are Associated With the Prognosis of Acute Respiratory Distress Syndrome After Sepsis - Hernández-Beeftink, Tamara; Guillen-Guio, Beatriz; Rodríguez-Pérez, Héctor; Marcelino-Rodríguez, Itahisa; Lorenzo-Salazar, Jose M.; Corrales, Almudena; Prieto-González, Miryam; Rodríguez-Pérez, Aurelio; Carriedo, Demetrio; Blanco, Jesús; Ambrós, Alfonso; González-Higueras, Elena; et al. (Frontiers in Immunology, 2021)
Acute respiratory distress syndrome (ARDS) is an inflammatory process of the lungs that develops primarily in response to pulmonary or systemic sepsis, resulting in a disproportionate death toll in Intensive Care Units (ICUs). Given its role as a critical activator of the inflammatory and innate immune responses, previous studies have reported that an increase of circulating cell-free mitochondrial DNA (mtDNA) is a biomarker for fatal outcomes in the ICU. Here we analyzed the association of whole blood mtDNA (wb-mtDNA) copies with 28-day survival from sepsis and sepsis-associated ARDS. We analyzed mtDNA data from 687 peripheral whole blood samples within 24 h of sepsis diagnosis from unrelated Spanish patients with sepsis (264 with ARDS) included in the GEN-SEP study. The wb-mtDNA copies were obtained from the array intensities of selected probes, with 100% identity with mtDNA and with the largest number of mismatches with the nuclear sequences, and normalized across the individual-probe intensities. We used Cox regression models for testing association with 28-day survival. We observed that wb-mtDNA copies were significantly associated with 28-day survival in ARDS patients (hazard ratio=3.65, 95% confidence interval=1.39-9.59, p=0.0087) but not in non-ARDS patients. Our findings support that wb-mtDNA copies at sepsis diagnosis could be considered an early prognostic biomarker in sepsis-associated ARDS patients. Future studies will be needed to evaluate the mechanistic links of this observation with the pathogenesis of ARDS.